Evaluasi Program Literasi Membaca di sekolah menengah pertama - Sumiyani Sumiyani (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine: (1) the effectiveness of the implementation of the reading literacy program in terms of the context component (X1) at SMPN 7 Tangerang City; (2) the effectiveness of the implementation of the reading literacy program on the input component of SMPN 7 Tangerang City; (3) the effectiveness of the implementation of the reading literacy program in terms of process components at SMPN 7 Tangerang City: (4) the effectiveness of the implementation of the reading literacy program in terms of product components at SMPN 7 Tangerang City; (5) the effectiveness of the implementation of the reading literacy program in terms of context (X1), input, process, and product components at SMPN 7 Tangerang City; (6) obstacles that hinder the implementation of the reading literacy program at SMPN 7 Tangerang City by using the CIPP evaluation method. Collecting data with a questionnaire filled out by 330 respondents. And the research sample was chosen randomly. The results showed: The evaluation of the implementation of the reading literacy program with the CIPP evaluation model was in the effective category.